(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
In Indonesia, LGBTQ+ individuals face widespread legal and social discrimination, including criminalization under existing laws and social exclusion due to cultural and religious norms. This paper examines the legal challenges LGBTQ+ individuals face in Indonesia, focusing on the legal framework, social stigma, and the role of civil society organizations in advocating for equal rights. Through a review of legal cases, government policies, and interviews with activists, the paper highlights the persistent barriers to legal recognition and protection for LGBTQ+ people, particularly in the context of Indonesia’s conservative societal norms. Despite challenges, LGBTQ+ advocacy groups have made significant strides in raising awareness and promoting social change. The research findings suggest that while legal reform remains elusive, societal attitudes toward LGBTQ+ people are slowly evolving, aided by grassroots activism and international support. The paper contributes to understanding the complex intersection of law, culture, and social change, providing recommendations for legal reforms and advocacy strategies to improve LGBTQ+ rights in Indonesia. This paper provides new insights into the legal and social struggles of LGBTQ+ individuals in Indonesia, offering a nuanced understanding of the barriers they face within a conservative context. The study advances LGBTQ+ rights research by examining the role of legal, cultural, and civil society dynamics in Indonesia, contributing to global discussions on LGBTQ+ advocacy and human rights in Southeast Asia.